Body image and eating patterns among adolescents - Bibiloni, Maria del Mar (BioMed Central, 2013)
BACKGROUND: Data on the association between body self-perception and eating patterns among adolescents are scarce. This study assessed the association between body image and eating patterns among normal-weight, overweight and obese adolescents. METHODS: A cross-sectional survey (n = 1231; 12–17 years old) was carried out in the Balearic Islands, Spain. Anthropometry, body image, socio-economic determinants, and food consumption were studied. RESULTS: Fifty-one percent of boys and sixty percent of girls that wished to be thinner had less than or equal to 3 eating occasions per day. Overfat girls that wish to be thinner skipped breakfast more frequently than normal-fat girls. Overfat boys and girls that wished a thinner body reported lower consumption of several food groups than normal-fat adolescents and overfat boys satisfied with their own body image (i.e. breakfast cereals, pasta and rice dishes, other oils and fats, high fat foods, soft drinks and chocolates in boys; and dairy products and chocolates in girls).A restriction of Western diet foods and energy intake was associated with a wish to be thinner among overfat adolescents. CONCLUSIONS: Many overfat boys were satisfied with their body image while practically all overfat girls reported wishing a thinner body. Meal patterns and food consumption were associated with body dissatisfaction and overfat status among adolescents.